2015
DOI: 10.1007/s00221-015-4394-6
|View full text |Cite
|
Sign up to set email alerts
|

Is there a link between sensorimotor coordination and inter-manual coordination? Differential effects of auditory and/or visual rhythmic stimulations

Abstract: The purpose of this study was to test how the sensory modality of rhythmic stimuli affects the production of bimanual coordination patterns. To this aim, participants had to synchronize the taps of their two index fingers with auditory and visual stimuli presented separately (auditory or visual) or simultaneously (audio-visual). This kind of task requires two levels of coordination: (1) sensorimotor coordination, which can be measured by the mean asynchrony between the beat of the stimulus and the correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In the TD group, it is interesting to note that auditory and visual stimuli lead to similar performance during learning. This result is quite surprising given that previous studies have found the dominance of auditory information in motor synchronization in healthy adults (Blais, Albaret, & Tallet, 2015; Chen et al., 2007; Fraisse, 1948; Patel et al., 2005; Repp & Penel, 2002; Semjen & Ivry, 2001; Tierney & Kraus, 2013) and in learning of complex rhythmic sequences (Karabanov et al., 2009). A first hypothesis is that children do not present such an auditory dominance.…”
Section: Discussionmentioning
confidence: 79%
“…In the TD group, it is interesting to note that auditory and visual stimuli lead to similar performance during learning. This result is quite surprising given that previous studies have found the dominance of auditory information in motor synchronization in healthy adults (Blais, Albaret, & Tallet, 2015; Chen et al., 2007; Fraisse, 1948; Patel et al., 2005; Repp & Penel, 2002; Semjen & Ivry, 2001; Tierney & Kraus, 2013) and in learning of complex rhythmic sequences (Karabanov et al., 2009). A first hypothesis is that children do not present such an auditory dominance.…”
Section: Discussionmentioning
confidence: 79%
“…This hypothesis was based on previous research reporting lower standard deviations with bimodal, compared to unimodal, stimuli. Although the magnitude of the difference between bimodal and unimodal stimuli varies between 2 ms (unimodal has smaller standard deviation) and −55 ms (bimodal has smaller standard deviation) (Elliott et al, 2010, 2011; Wing et al, 2010; Wright et al, 2014; Blais et al, 2015; Roy et al, 2017), prior results generally indicate performance is better with bimodal stimuli. Here, the difference between bimodal and unimodal stimuli was −6 ms (Figure 5H), in line with previous results.…”
Section: Discussionmentioning
confidence: 97%
“…Fortunately, this result is not without precedent. Studies assessing asynchrony typically show either bimodal is comparable to the best unimodal asynchrony or that bimodal is between the two unimodal asynchronies (Wing et al, 2010; Wright et al, 2014; Blais et al, 2015; Roy et al, 2017). Here, we show the former using absolute asynchrony (Figure 5G).…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, the production of time intervals can be assessed via sensori-motor synchronization (SMS), which is synchronization of a motor output with a sensory stimulus (Fraisse, 1948;Fraisse et al, 1958;Repp et al, 2011;Repp, 2005;Repp and Su, 2013). Several studies have investigated SMS with isochronous stimuli, i.e., with identical time intervals between two stimuli (Jäncke et al, 2000;Chen et al, 2002;Pollok et al, 2009;Blais et al, 2014Blais et al, , 2015. Studies using an SMS paradigm in healthy adults highlight that synchronization with auditory stimuli is stable (Sowiński and Dalla Bella, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the literature shows that SMS depends on the sensory modality of the stimuli. When participants are required to tap with their index finger in synchronization with tones (auditory sequence) or flashes (visual sequence), SMS with an auditory stimulus is more accurate and stable than SMS with a visual stimulus (Fraisse, 1948;Semjen and Ivry, 2001;Chen et al, 2002;Repp and Penel, 2002;Patel et al, 2005;Tierney and Kraus, 2013;Blais et al, 2014Blais et al, , 2015. This suggests that rhythmic movements tend to synchronize with auditory more than visual rhythms (Repp and Penel, 2004;Kato and Konishi, 2006).…”
Section: Introductionmentioning
confidence: 99%